1999
DOI: 10.1128/jvi.73.4.3284-3291.1999
|View full text |Cite
|
Sign up to set email alerts
|

The U69 Gene of Human Herpesvirus 6 Encodes a Protein Kinase Which Can Confer Ganciclovir Sensitivity to Baculoviruses

Abstract: The protein encoded by the U69 open reading frame (ORF) of human herpesvirus 6 (HHV-6) has been predicted to be a protein kinase. To investigate its functional properties, we have expressed the U69 ORFs from both HHV-6 variants, A and B, by using recombinant baculoviruses (BV6AU69 and BV6BU69). Nickel agarose and antibody affinity chromatography was used to purify the proteins to homogeneity and when incubated with [γ-32P]ATP, both U69 proteins became phosphorylated on predominantly serine residues. These data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Previous results had already shown that the BGLF4 protein phosphorylates histones in in vitro kinase assays [206]. In fact, there are several examples of viral kinases capable of histone (usually H1 or H2B) phosphorylation in vitro, including HCMV UL97 [207], human herpesvirus 6 U69 [208], HSV-2 UL13 [209] as well as KSHV and MHV-68 viral cyclin/ cyclin-dependent kinase complexes [210][211][212][213]. However, the lack of in vivo data makes any conclusion about the actual relevance of these observations impossible.…”
Section: Histone Phosphorylation and Other Histone Modificationsmentioning
confidence: 99%
“…Previous results had already shown that the BGLF4 protein phosphorylates histones in in vitro kinase assays [206]. In fact, there are several examples of viral kinases capable of histone (usually H1 or H2B) phosphorylation in vitro, including HCMV UL97 [207], human herpesvirus 6 U69 [208], HSV-2 UL13 [209] as well as KSHV and MHV-68 viral cyclin/ cyclin-dependent kinase complexes [210][211][212][213]. However, the lack of in vivo data makes any conclusion about the actual relevance of these observations impossible.…”
Section: Histone Phosphorylation and Other Histone Modificationsmentioning
confidence: 99%
“…Acyclovir and other thymidine kinase-dependent drugs, however, are only marginally effective (Agut et al, 1989;Burns & Sandford, 1990;Yoshida et al, 1998). The HHV-6 U69 gene product, the presumed functional homologue of HCMV UL97, phosphorylates ganciclovir (Ansari & Emery, 1999;De Bolle et al, 2002). A HHV-6 mutant exhibiting decreased sensitivity to ganciclovir in vitro was isolated after serial passages in the medium containing the drug; this mutant was later found to encode mutations in the U69 gene (Manichanh et al, 2001).…”
Section: Treatmentmentioning
confidence: 99%
“…Since the identification of the CMV UL97-encoded protein kinase as the enzyme responsible for the activation of ganciclovir in CMV-infected cells [33], the homologous HHV-6 protein (pU69) has been thought to play a similar role in the activation of ganciclovir in HHV-6-infected cells. Ansari and Emery [34] demonstrated that the HHV-6 U69encoded serine/threonine kinase, when expressed in baculovirus, is able to confer ganciclovir sensitivity. In order to directly measure the HHV-6 pU69-catalysed phosphorylation of ganciclovir in human cells, we have recently cloned the U69 gene into vaccinia virus, according to a strategy that was originally developed for CMV UL97 [35].…”
Section: Antiviral Therapy For Hhv-6 Infectionsmentioning
confidence: 99%
“…Their homologous counterparts in EBV, HHV-6, HHV-7 and HHV-8 have either not been established (HHV-7) or have remained less well defined as far as the substrate specificity is concerned (HHV-6, HHV-8 and EBV). For HHV-6, we have already described the interaction of ganciclovir with the HHV-6 U69-encoded kinase [34], and for HHV-8 we addressed the ORF-21-and ORF-36-encoded kinases also with respect to ganciclovir as substrate [70,71]. The substrate specificity of the EBV BXLF-1-encoded TK is definitely narrower than that of its HSV-1, HSV-2 and VZV homologues: it would have good affinity for brivudin, but only poor activity for the acyclic nucleoside guanosine analogues acyclovir, ganciclovir and penciclovir [77][78][79].…”
Section: Role Of Virus-induced Kinases In the Activity Of Nucleoside mentioning
confidence: 99%